Carbon stock change dynamics of oil palm plantation in Sembilang Dangku Landscape, South Sumatra. (October 2019) - Rachdian, Azar; Hariyadi; Setiawan, Yudi; Santoso, Kresno Dwi
Abstract: One of the land cover type in the Sembilang Dangku Landscape is oil palm plantation, which is developed by changing the type of previous land covers. Land cover change causes changes in carbon stock. If the carbon stock increase in an area, it means the area acts as a carbon sinker, whereas if the carbon stock decrease, inconsequently the area is a carbon emitter. The purpose of this study was to analyze the dynamics of carbon stock changes in 1997-2007 and 2007-2017. The research was carried out on six private oil palm plantations. Carbon stocks were estimated based on the type of land cover interpreted from Landsat 5 imagery with the unsupervised method by using Las Palmas QGIS 2.18.0 Software. Determination of land cover in 1997 was based on the year when oil palm plantation began. Carbon stock of oil palm plantation was estimated based on the Normalized Difference Vegetation Index (NDVI) with the equation: Y = 638.13 X - 242.65 (Y = carbon stock, X = NDVI). The value of carbon sequestration or carbon emission were based on carbon stock changes. The types of land cover in 1997 and 2007 were in the form of shrub swamp, oil palm plantation, undisturbed peat swamp forest, disturbed peat swamp forest; while in 2017 land cover was dominated by oil palm plantation. The results showed respectively that carbon stocks in 1997, 2007 and 2017 were 3, 333, 549.6 tonC, 1, 541, 825.5 tonC, and 1, 626, 951.8 tonC. In 1997-2007, carbon stock encountered a decrease, resulting in carbon emission of 18.68 tonCO2 -eq/ha/year. However, in 2007-2017, carbon stock encountered an increase, leading in carbon sequestration of 0.89 tonCO2 -eq/ha/year.